Empowerment and creativity of the consumer, in the dynamics of new media and communication models - Ortiz Lizardi, Ilia de los Ángeles (2022)
Ecological and local markets emerge as an option where both producers and consumers can maximize their benefits while deciding to participate in ecological behaviors such as maintaining production processes with low environmental impact, adequate waste management and the reduction of pollutants discharged into the environment, which gives added value to the benefit of the local producer for maintaining their healthy environment. Meanwhile, the consumer can maximize their usefulness through the purchase of products that cover their consumption needs, but also provide additional utility based on their ecological attributes, valued by this type of consumers who appreciate these attributes as health benefits or environmental safety. The truth is that organic and local products have been able to increase their diffusion thanks to the structures of the new media that allow rethinking the roles of consumers and producers: the consumer is understood as an active individual, capable of identifying ideologically with products, behaviors, media content and in general ecological lifestyles, mainly,  due to the possibility that information and communication technologies offer for the search, distribution and circulation of ecological information for comparison in making consumer decisions, going beyond the simple purchase of products, reinforcing new cultural dynamics (in the sense of a culture made in everyday actions), supported by the means of the current centenary. Therefore, the producer must be a creative individual who seeks, through new media technologies, to satisfy the demands of his audience since he is subject to a more immediate interaction with it, which requires him to create content aimed at the generation of prosumers with an environmentally friendly consumption style that has been empowered by the new media of the digital Age.